Graphene oxide nanoplatelets potentiate anticancer effect of cisplatin in human lung cancer cells - Nur Farhanah Rosli (2021)
Graphene oxide (GO) has been widely explored by many in drug delivery strategies and toxicity assays. The toxicity of graphene oxide depends on the size of the sheets. Smaller sheets show lower toxicity, a quality which is essential for utilization in biomedical applications. However, despite vast research on GO, anticancer properties and drug carrier capabilities of graphene oxide nanoplatelets have yet to be fully explored. Herein, we have uniquely prepared graphene oxide nanoplatelets (GONPs) from well-defined stacked graphite nanofibers (SGNF) with a base of 50 × 50 nm2 for toxicity and drug potentiation studies when coadministered with the chemotherapeutic drug cisplatin (CP) in human lung cancer cells, A549 cells. Results obtained from our studies have found that not only were GONPs able to act as drug carriers, but they can also significantly potentiate anticancer effect of CP in A549 cells.